Housing as a determinant of health equity: A conceptual model - Swope, Carolyn B.; Hernández, Diana (Social science & medicine (1982), 2019)
Housing is a major pathway through which health disparities emerge and are sustained over time. However, no existing unified conceptual model has comprehensively elucidated the relationship between housing and health equity with attention to the full range of harmful exposures, their cumulative burden and their historical production. We synthesized literature from a diverse array of disciplines to explore the varied aspects of the relationship between housing and health and developed an original conceptual model highlighting these complexities. This holistic conceptual model of the impact of housing on health disparities illustrates how structural inequalities shape unequal distribution of access to health-promoting housing factors, which span four pillars: 1) cost (housing affordability); 2) conditions (housing quality); 3) consistency (residential stability); and 4) context (neighborhood opportunity). We further demonstrate that these four pillars can lead to cumulative burden by interacting with one another and with other structurally-rooted inequalities to produce and reify health disparities. We conclude by offering a comprehensive vision for healthy housing that situates housing's impact on health through a historical and social justice lens, which can help to better design policies and interventions that use housing to promote health equity. •Healthy housing spans four pillars–conditions, cost, consistency, and context.•Housing disparities have social and historical roots that perpetuate vulnerability.•Housing problems across pillars have multiplicative deleterious health effects.•Future interventions must address multiple housing domains to advance health equity.